Evaluasi Faktor Adopsi Jkn Mobile Di Kabupaten Muaro Jambi Dengan Menggunakan Metode Utaut (Unified Theory Of Acceptance And Use Of Technology) Dan Metode Technology Acceptance Model (Tam): JKN Mobile, UTAUT, TAM, Adopsi Aplikasi, SmartPLS 4 - Lisa Oktariani; Setiawan Asegaf; Joni Devitra (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
This study evaluates the adoption factors of the JKN Mobile application in Muaro Jambi Regency using the UTAUT (Unified Theory of Acceptance and Use of Technology) and TAM (Technology Acceptance Model) methods. The research aims to identify the factors influencing JKN Mobile adoption and compare the two models to determine which one better explains the adoption of this application. This study involved 393 respondents who are JKN Mobile users in Muaro Jambi Regency. Data were collected through questionnaires distributed online. Data analysis was performed using the Structural Equation Modeling (SEM) method with the help of SmartPLS software. The results showed that the UTAUT model has a better predictive ability in explaining JKN Mobile adoption compared to the TAM model. In the UTAUT model, the Facilitating Conditions (FC) factor has the strongest influence on User Behavior (UB). In addition, the Performance Expectancy (PE) and Social Influence (SI) factors also significantly affect Behavioral Intention (BI). Meanwhile, in the TAM model, the Perceived Ease of Use (PEOU) factor significantly affects Perceived Usefulness (PU) and Behavioral Intention to Use (BIU). Perceived Usefulness (PU) also proved to significantly affect Behavioral Intention to Use (BIU). This study provides practical implications for JKN Mobile application developers and related parties to pay more attention to the factors identified by the UTAUT and TAM models in an effort to increase application adoption.